'An indispensable aid': Urban mobility, networks and the guidebook in Bristol, 1900–1930. (January 2023) - Ferriday, Lena
Abstract: This article introduces a new perspective on the urban guidebook, playing with the concept of the network to demonstrate the genre's value for spatial research. Using early twentieth century Bristol as a case study, it examines the collaborative relationship between guidebooks and transport networks to shed light on the dynamic, multivalent characteristics of human movements through the city. Using mapping methodologies, the article reveals guidebook texts' spatial characteristics which contributed to the material makeup of the city's mobility geography. It also explores how the genre highlighted subjectivity, and thus played a crucial role in elaborating the meanings and cultures of movement which have concerned mobility geographers. Overall, the article contends to the active role played by the guidebook in Bristol, in doing so elaborating its significance for urban geographers interrogating the richness and diversity of past mobilities. Highlights: Guidebooks have historically played a key role in shaping urban mobility. Mapping reveals the spatial connections between textual and vehicular urban networks. Guidebooks expose the layers of culture hidden in mobile systems. The concept of the urban network should incorporate non-material forces. The guidebook is a valuable source for mobility geographers examining urban pasts.